The Prevalence of the Burnout Syndrome and Factors Associated in the Students of Dentistry in Integral Clinic: A Cross-Sectional Study - Luis Alberto Chauca Bajaña; Luis Campos Lascano; Lourdes Jaramillo Castellon; Carlos Carpio Cevallos; Gabriela Cevallos-Pozo; Byron Velasquez Ron; Fábio França Vieira e Silva; Mario Perez-Sayans (Hindawi Limited, 2023)
Background. Burnout syndrome (BS) is composed of three interrelated dimensions (emotional exhaustion, depersonalization, and personal fulfillment), and it has been documented that it affects health professionals from an early age. Aims. Determine the prevalence of BS and associated factors in the integral clinic of the Dentistry Pilot School. Material and Methods. Two instruments were applied: (1) Maslach Burnout Inventory, which measures the degree of professional burnout through 22 items that describe the professional's attitudes and feelings toward work, as well as symptoms associated with this phenomenon; (2) the second questionnaire determines the possible symptoms of BS and consists of 14 questions that describe tiredness, sleep problems, digestive problems, respiratory problems and headaches, temporomandibular joint (TMJ), neck pain, back pain, and upper and lower extremity pain. The instruments were answered anonymously by a total of 300 students who participated in the study. Results. The emotional exhaustion of the participants was 48.3% at a higher level, the depersonalization was 46.7% at a higher level, and the low perception of personal fulfillment was 73%. In addition, it was shown that BS is significantly related to marital status (p<0.001∗), with single people reporting being more exhausted, with the 6-month level (p=0.011) and with the following symptoms: non-neck pain, head, TMJ, back, waist, upper and lower body pain. Conclusion. It was found that the BS had a prevalence of high levels of exhaustion and depersonalization correlated with the marital status and level of preparation (academic degree) of the person, finding a prevalence of symptoms such as pain in the neck, head, TMJ, and back.